Wild desires & mistaken identities: lesbianism and psychoanalysis - O'Connor, Noreen; Ryan, Joanna (Columbia University Press, 1993)
This groundbreaking book provides a challenging exploration of psychoanalytic ideas about lesbians and lesbianism. Based on the authors' clinical experience as psychoanalytic psychotherapists, it offers a new and thoughtful framework that does not inevitably pathologise or universalise all lesbianism. A wide range of psychoanalytic ideas are surveyed, from Freud, Deutsch and Jung to Lacan and contemporary object-relations theorists. Questions on sexual identity, sexual desire and gender identity, of transference and countertransference, and also of institutional practices in relation to training, are all critically - and stimunlatingly - addressed.
Section: 315 p.
Keywords: LGBTQIA2+; approches et analyses; cours; discipline; désir lesbien; lesbianisme; premier cycle; psychanalyse; sciences humaines; sexualité; soc2014; thématiques